PENINGKATAN HASIL BELAJAR BOLA VOLI MELALUI PERMAINAN BOLA VOLI TABIR DI KELAS XI TKR 2 SMK SULTAN FATAH DEMAK TAHUN PELAJARAN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
This study aimed to know the improvement of volleyball learning achievement of grade XI student of SMK Sultan Fatah TKR 2 Demak. This study used action research. In the implementation, there were two cycle, where on each cycle will see the improvement of volleyball learning achievement. The subjects were students of grade XI TKR 2 SMK Sultan Fatah Demak totaling 29 students. In gathering the data, obtained from observations of learning and documentation. Based on the research results, the percentage results of absorbed material in the first cycle were psychomotoric aspect 72.4%, cognitive aspect 72.41%, affective aspect 91.03% increased, while in the second cycle became, psychomotoric aspect 78.44%, cognitive aspect 75.86%, affective aspect of 93.79%. In the first cycle the learning achievement that can be passed the KKM were 62.07% of all of the students, in the second cycle increased to 93.1% of the total number of students. Based on the research results, it can be concluded that volleyball learning through play veil volleyball can improve volleyball learning achievement in class XI student of SMK Sultan Fatah TKR 2 Demak.